Miniaturized CSRR TAG Antennas for 60GHz Applications - O. Ncibi; Abdelhak Ferchichi; TP. Vuong; A. Gharsallah (Institute of Advanced Engineering and Science, 2014)
In this paper, a novel approach to design an antenna for a transponder inradio frequency identification (RFID) is proposed. This approach is based onusing a slot-ring antenna with a coplanar waveguide excitation integratedantennas in silicon technology. The RFID frequency chosen is the worldwideavailable free 60-GHz band .The structure is simulated by using ComputerSimulation Technology (CST). The antenna size is 1.5 × 1.3 mm2. Thisproposed antenna presents a gain about 3.82 dB which means a possibility toincrease the readable range.DOI:http://dx.doi.org/10.11591/ijece.v4i1.4724